PENINGKATAN PELANGGAN PADA PT. TELKOMSEL SUMBAWA MELALUI PENERAPAN STRATEGI RELATIONSHIP MARKETING - Sawiliyah, S; Kamaruddin, K; Kurniawansyah, K (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This study aims to know the effect of relationship Marketing on increasing the number of customers at PT. Telkomsel Sumbawa. The type of study used in this study was associative approach which aims to determine the relationship between variables and verify whether a variable causes the variable to change or not. The type of data used in this study was quantitative data in the form of scoring results of respondents' answers regarding the object under study. This quantitative data was obtained directly from the original source, namely research respondents who were collected using a research instrument in the form of a questionnaire. The number of samples used as respondents in this study was 100 people who were selected using accidental sampling techniques. The data that has been collected was processed using the SPSS application to be studied using simple linear regression analysis techniques, partial hypothesis testing (t test), and determinant coefficient test (R2). The results of this study showed the relationship marketing had a positive and significant effect on increasing the number of customers at PT. Telkomsel Sumbawa. The effect of relationship marketing on increasing the number of customers at PT. Telkomsel Sumbawa was 36.1%, while the remaining of 63.9% was affected by other variables outside this study, such as product quality, service quality and customer satisfaction.